Analisis Faktor - Faktor yang Mempengaruhi Kadar Asam Urat pada Pekerja Kantor di Desa Karang Turi, Kecamatan Bumiayu, Kabupaten Brebes - Tahta, Andri; Saryono,; Upoyo, Arif Setyo (Jurusan Keperawatan FIKES UNSOED, 2009)
Hiperuricemia is one of strong predictor to the cardiovascular mortality. Hiperuricemia was caused by high purin synthetic because of not in orderly diet and interference of uric acid excretion process. Several factors are predict associate with uric acid level increased. This research aimed to know several factors that influence uric acid level in office workers in Karang Turi countryside, Bumiayu subdistric, Brebes Regency.The correlation between the factors and uric acid level use analitic method with cross sectional. 50 people were taken as the sample. Conclusion: the purin consumption, alkohol consumption, activity and age were not related with uric acid level in office worker in Karang Turi Countryside, Bumiayu Subdistric, Brebes Regency.